2017
DOI: 10.1111/cge.12970
|View full text |Cite
|
Sign up to set email alerts
|

BMP15 “knockout‐like” effect in familial premature ovarian insufficiency with persistent ovarian reserve

Abstract: Premature ovarian insufficiency (POI) affects 1% to 2% of women under 40 years. Bone morphogenetic protein 15 (BMP15) variants have been described in POI. We studied a family with 2 sisters compound heterozygous for deletions in the BMP15 gene on chromosome Xp11.22 yielding a human "knockout-like" effect: a c.151_152delGA deletion yielded a p.Glu51IlefsTer27 mutation transmitted by the hemizygous father and a c.189_198delAGGGCATTCAinsTG deletion/insertion yielded a p.Glu64AlafsTer12 mutation transmitted by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 12 publications
2
14
1
Order By: Relevance
“…A similar underlying mechanism has been observed in case of naturally occurring BMP15 mutations in the “Grivette” and “Olkuska” sheep, which would mainly have an effect on the BMP15‐GDF9 heterodimer signaling (Demars et al, 2013). As GDF9 is pivotal for the initiation of primordial follicle growth (Vitt et al, 2000) and no GDF9 variants have been found in our patients, the recruitment of primordial follicles from the resting pool into the growth phase would still be possible even in the absence of BMP15 , as demonstrated by the occurrence of spontaneous menarche in Patient A, and recently suggested by other authors (Mayer et al, 2017). However, the absence of the concurrent action of the heterodimer would then lead to a dysregulated progression of folliculogenesis and a premature complete exhaustion of the impaired ovarian reserve.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A similar underlying mechanism has been observed in case of naturally occurring BMP15 mutations in the “Grivette” and “Olkuska” sheep, which would mainly have an effect on the BMP15‐GDF9 heterodimer signaling (Demars et al, 2013). As GDF9 is pivotal for the initiation of primordial follicle growth (Vitt et al, 2000) and no GDF9 variants have been found in our patients, the recruitment of primordial follicles from the resting pool into the growth phase would still be possible even in the absence of BMP15 , as demonstrated by the occurrence of spontaneous menarche in Patient A, and recently suggested by other authors (Mayer et al, 2017). However, the absence of the concurrent action of the heterodimer would then lead to a dysregulated progression of folliculogenesis and a premature complete exhaustion of the impaired ovarian reserve.…”
Section: Discussionsupporting
confidence: 75%
“…Notably, the mother was heterozygous for only one of these mutations and had a normal fertility. Therefore, this family did not support previous reports of BMP15 haploinsufficiency and gene dosage in humans (Mayer, Fouquet, Pugeat, & Misrahi, 2017). Here, we obtain insights on these open questions by: (a) the description of two BMP15 null homozygous variations in two girls with POI and primary amenorrhea confirming that BMP15 haploinsufficiency is not sufficient to cause POI; (b) comprehensive molecular studies on previously described variants in the precursor or mature BMP15 peptide (Wang, B., Wen, et al 2010), suggesting that heterozygous missense variants can predispose to POI by interfering with the cumulin activity.…”
Section: Introductioncontrasting
confidence: 90%
“…Additional genetic mutations in an oligogenic mode of inheritance and/or environmental factors must be involved. Despite streak ovaries, AMH was initially detectable in the two POI sisters bearing both deletions of BMP15, supporting the presence of an OR [120]. Five years later, however, AMH was not detected in both sisters, probably because of exhaustion of the PF pool, and one sister had received an egg donation.…”
Section: Genes Involved In Establishment Of the Pf Pool And Maturatiomentioning
confidence: 76%
“…It was also proposed that reduced BMP15 dosage would contribute to the ovarian phenotype of Turner syndrome patients [119]. These conclusions were challenged by a very recent work on a family with a BMP15 knockout-like effect [120], with both parents bearing deletions in the proregion of the BMP15 precursor. The heterozygous mother conceived normally and had three children.…”
Section: Genes Involved In Establishment Of the Pf Pool And Maturatiomentioning
confidence: 99%
“…A study from 2010 on Chinese POI patients showed the identification of a missense mutation in BMP15 in the mature region (R329C) that might impair the correct folding and final three-dimensional structure of BMP15 subunit as well as the formation of homo- or heterodimers with GDF9 (Wang et al, 2010). A more recent study was published on a family with two sisters who exhibited to be compound heterozygous with E51IfsTer27 inherited from their father and E64AfsTer12 from their mother (Mayer et al, 2017). Due to frame-shift mutations, both of these mutant BMP15 proteins are prematurely truncated in the proregion, precluding mature BMP15 production.…”
Section: Gdf9 and Bmp15 In Dizygotic Twinning Poi And Pcosmentioning
confidence: 99%